Hydroxyapatite-doped coatings with antimicrobial properties by matrix assisted pulsed laser evaporation - Rădulescu, Diana Elena; Vasile, Bogdan Ștefan; Surdu, Vasile Adrian; Trușcă, Roxana Doina; Bîrcă, Alexandra Cătălina; Ilie, Cornelia Ioana; Dițu, Lia Mara; Motelică, Ludmila; Neacșu, Ionela Andreea; Boerașu, Iulian; Brajnicov, Simona; Codrea, Cosmin Iulian; et al. (Elsevier B.V., 2025)
The development of bioactive coatings that improve implant performance is critical due to bacterial colonization, biofilm formation, foreign body responses, and inadequate tissue integration for biomedical applications. To address these issues, this study aimed to synthesize and characterize hydroxyapatite (HAp) coatings derived from biogenic sources (eggshells and mussel shells). Both unsubstituted and Mg2+, Sr2+, and Cu2+-substituted HAp materials were synthesized and deposited on three different substrates: two magnesium-based alloys and titanium. Structural and chemical analyses using X-Ray Diffraction (XRD) and Fourier-Transform Infrared Spectroscopy (FTIR) confirmed successful HAp formation, while Scanning Electron Microscopy (SEM) revealed morphological variations influenced by the biogenic source and dopant concentration. XRD analysis showed that Cu2+ doping reduced crystallinity by 15–20 % compared to undoped HAp, while Mg2+ and Sr2+ maintained structural integrity within 5 % of undoped samplesAccording to biological evaluations, Mg substrates (I and II) reduced S. aureus biofilms by up to 8 CFU/mL, while the titanium substrate (III) demonstrated 25–30 % higher cell viability compared to Mg substrates. Further, substrate II increased its biocompatibility by 33 % from 24h to 48h (120 %–160 %). Mg2+ and Sr2+ substitutions enhanced cell proliferation, while Cu2+ presented a dose-dependent cytotoxicity. These findings suggest that biogenic HAp coatings, with personalized composition and substrates, have good potential as multifunctional materials for inhibiting bacterial colonization and promoting osseointegration, offering valuable insights for tissue engineering and regenerative medicine.
Keywords: Hydroxyapatite; Ion substitution; Bioactivity; Coatings; MAPLE; Eggshells; Mussel shells; Biofilm